Bra Usage Duration and Breast Cancer Risk: A Case-Control Study - Dhito Dwi Pramardika; Meityn Disye Kasaluhe; Siti Barokah (Poltekkes Kemenkes Palu, 2023)
Introduction: Breast cancer is a disease feared by most women, with 2.3 million women worldwide being diagnosed with this disease. In 2024, Indonesia will relocate its capital to East Kalimantan Province, which currently has the second-highest (1%) prevalence of breast cancer cases in Indonesia. Objective: Given the increasing prevalence of breast cancer, it is worthwhile to scientifically examine the relationship between the duration of bra usage, age at first bra usage, bra size suitability, and types of bras used in relation to the occurrence of breast cancer. Method: The study design used was a case-control study with a 1:1 ratio of 48 respondents (24 cases and 24 controls) selected through purposive sampling. The analysis employed chi-square and odds ratio tests. Results: The study revealed that the average age of the respondents was 45.25 years. Furthermore, the variables of bra usage duration (OR=2.333), age at first bra usage, bra size suitability, and bra type (OR=0.639) showed no association with the occurrence of breast cancer (α>0.05). Conclusion: This research concludes that there is no association between bra usage and the occurrence of breast cancer in women in East Kalimantan Province. Recommendation: It is suggested to reduce the duration of bra usage to less than 24 hours to minimize the risk factors for breast cancer.